The Posthumanist Turn in the Interdisciplinary Research Field of Childhood Studies – Response to the Environmental Problems of Modern Times - Kowalik-Olubińska, Małgorzata (INSTED: Interdisciplinary Studies in Education & Society, 2024)
The purpose of the article was to discuss the shift towards post-humanism taking place in the Childhood Studies research field, which is seen by its creators as the answer to the environmental problems of modern times. The penetration of posthumanist thought into the Childhood Studies field has resulted in a turn towards a relational ontology. Childhood has been recognised as a phenomenon closely linked to nature, and the child as a relational being, existing in communities of interrelated human and non-human entities. Drawing on posthumanist thinking has also helped to recognise the need to refer to ideas of community, relationality, and becoming/becoming-with in educational contexts. This resulted in the transition to pedagogical approaches that enable children to learn and stand together with the world, while also building in-depth relationships with both human and non-human entities. According to the author, strengthening children’s disposition in this respect will enable them to coexist with all entities and Prosper in common worlds. This will increase the chances of all of us to successfully dealing with the environmental threats of modern times.